(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
The article presents theoretical foundations, practical ways and methodical recommendations for implementing differential approach in education. The differential approach allows you to effectively organize the educational process, taking into account the individual capabilities, level of knowledge and interests of each student. With this approach, learners can demonstrate their full potential and achieve good results.